Exploring the factors influencing Chinese civil engineering students' willingness to continuously use the Bilibili online platform: innovative integration model based on UX, TAM, and ECM - Zhao, Yi; Yang, Yang; Guo, Zhengxing (Frontiers in Education, 2025)
Learning via online platforms is gaining traction among university students globally. Prior research has demonstrated that students pursuing majors in medicine, linguistics, and computer science have reaped benefits from online learning platforms. Will Chinese students persist in utilizing online platforms for ongoing learning? This study establishes a novel model, drawing on data from 435 undergraduate students majoring in civil engineering in China. This model amalgamates user experience, the Technology Acceptance Model (TAM), and the Expectation Confirmation Model (ECM), providing an in-depth analysis of the factors influencing the willingness to continue using the Bilibili online platform. The findings reveal that: (1) the new model exhibits good fit; (2) 12 out of 13 hypotheses are supported, with functional experience showing no significant influence on satisfaction and intention to continue using; (3) perceived ease of use has a more pronounced impact on satisfaction and intention to continue using compared to perceived usefulness